2011
DOI: 10.1007/s00134-011-2257-6
|View full text |Cite
|
Sign up to set email alerts
|

Rule of rescue or the good of the many? An analysis of physicians’ and nurses’ preferences for allocating ICU beds

Abstract: More than one-third of ICU clinicians forewent substantial social benefits so as to devote resources to an individual patient unlikely to benefit from them. Such allegiance to the rule of rescue suggests challenges for efforts to reform ICU triage practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 29 publications
0
25
0
1
Order By: Relevance
“…For many patients, particularly those who require life-sustaining therapies, ICU admission is required to rescue patients from imminent death. 29 However, past work demonstrates that ICU admission may be more discretionary for patients at lower risk. 4,5,30 Chen et al 30 evaluated patients admitted to Veterans Administration hospitals and found signifi cant variation in ICU admission rates between hospitals that persisted aft er adjustment for both predicted mortality on admission and admission diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…For many patients, particularly those who require life-sustaining therapies, ICU admission is required to rescue patients from imminent death. 29 However, past work demonstrates that ICU admission may be more discretionary for patients at lower risk. 4,5,30 Chen et al 30 evaluated patients admitted to Veterans Administration hospitals and found signifi cant variation in ICU admission rates between hospitals that persisted aft er adjustment for both predicted mortality on admission and admission diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Kohn and colleagues [67] sent questionnaires to a national sample of US ICU clinicians, soliciting their preferences for allocating their last bed to a gravely ill patient with little chance of surviving versus a deceased or dying patient for whom aggressive management could help others through organ donation. The authors received completed surveys from 684 of 2,206 physicians (31%) and 438 of 988 nurses (44%).…”
Section: Ethical and Legal Issuesmentioning
confidence: 99%
“…This system exceeds the ability of any clinician to tailor patient management and assess their likelihood of survival. It is also free from bias stemming from the rule of rescue [2]. Triage is performed by this computerized system, with patients being admitted to the ICU only if data indicate that they will respond to treatment: if their telomeres demonstrate a tendency for longevity [3], their genetic testing demonstrates that they are not likely to develop non-iatrogenic complications; e.g.…”
Section: "Prediction Is Very Difficult Especially About the Future" mentioning
confidence: 99%